Benthic foraminifera in surface sediments in the Maricá lagoon, Rio de Janeiro State - Bomfim, Clarissa da Silva; Vilela, Claudia Gutterres; Guedes, Daniel Coré (Anuário do Instituto de Geociências, 2010)
A study of benthic foraminifera was carried out on sediments from the bottom of Maricá lagoon located in the Região dos Lagos, state of Rio de Janeiro. This region is suffering with disordered human occupation and there has been an increase in the occupation rates and several projects for tourist resorts in the area. The response of the foraminifera to such activities was important for the ecological characterization. The laboratory treatment of the samples followed the specific methodology for foraminifera. The dominant species were Miliammina fusca and Miliammina spp., followed by Haplophragmoides spp., Trochammina inflata, Trochammina spp, Ammobaculites dilatatus and Arenoparrella mexicana. Those species have agglutinated tests that characterize paralic environments with low energy and salinity variations, in coastal regions. A comparative study with the Guanabara Bay showed distinct assemblages and distinct environments. In spite of the anthropogenic pollution influence in the lagoon, that pollution has not reached critical levels, and this response could suggest an efficient environment control by public policies to preserve the ecosystem.